Preparation and Characterization of Adsorbent from Natural Zeolite Mixed Chicken Feather in Degradation of Batik Waste Dyes Based Green Chemistry - Rais Nur Latifah (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2021)
This research is the adsorption of dyestuffs from batik industry waste. The adsorption method was used chicken feather adsorbent with natural zeolite. Zeolite was activated by HF. Feather flour was activated with 0.2 M KOH. The main focus of this research is determine the potential for dye degradation with the batch method.Samples were analyzed by Atomic Absorption Spectroscopy (AAS), Fourier Transform Infra Red Spectrophotometer (FTIR), and Surface Area Analyzer (SAA). Measurement of dye degradation includes the effect of adsorbent concentration, pH, contact time and particle size of adsorbent. The results showed that the optimum pH in the degradation of dyestuffs from the batik industry waste was pH 8.5. The optimum contact times by activated and unactivated adsorbents were 65 minutes and 120 minutes, respectively. The reaction kinetics analysis showed the Freundlich adsorption model based on the experimental data. This indicates that the surface pores of the adsorbent are very influential in the degradation of the dye. Adsorption capacity of degradation dyestuffs with adsorbents has an efficiency of 94%. In the laboratory, it has been proven that adsorbents are able to degrade dyes in batik waste before being discharged into the water disposal system.